Control of cucumber (Cucumis sativus L.) tolerance to chilling stress—evaluating the role of ascorbic acid and glutathione - Lukatkin, Alexander S.; Anjum, Naser A. (Frontiers in Environmental Science, 2014)
Chilling temperatures (1-10 ºC) are known to disturb cellular physiology, cause oxidative stress via creating imbalance between generation and metabolism of reactive oxygen species (ROS) leading finally to cell and/or plant death. Owing to known significance of low molecular antioxidants - ascorbic acid (AsA) and glutathione (GSH) in plant stress-tolerance, this work analyzes the role of exogenously applied AsA and GSH in the alleviation of chilling stress (3°C)-impact in cucumber (Cucumis sativus L. cv. Vjaznikowskij 37) plants. Results revealed AsA and GSH concentration dependent metabolism of ROS such as superoxide (O2•‾) and the mitigation of ROS-effects such as lipid peroxidation (LPO) as well as membrane permeability (measured as electrolyte leakage) in C. sativus leaf discs. AsA concentration (750 µM) and GSH (100 µM) exhibited maximum reduction in O2•‾ generation, LPO intensity as well as electrolyte leakage, all of these were increased in cold water (3°C and 25°C)-treated leaf discs. However, AsA, in particular, had a pronounced antioxidative effect, more expressed in case of leaf discs during chilling (3°C); whereas, at temperature 25°C, some AsA concentrations (such as 50 and 100 mM AsA) exhibited a prooxidative effect that requires molecular-genetic studies. Overall, it is inferred that AsA and GSH have high potential for sustainably increasing chilling-resistance in plants.